Amino acids and biogenic amines determination in Mystus nemurus. - Widjaja, Willy Pranata; AS, Abdel Ameer; Abu Bakar, Fatimah; Saari, Nazamid; Ishak, Zamri; Harith, Hanis Hazeera (Wiley, 2011)
The concentration of biogenic amines, i.e., histamine, putrescine, and cadaverine were studied as indicators of Mystus nemurus muscle quality under different storage conditions, namely, ambient (28±2C), chilled (10±2C) and in iced (2±1C) temperature. The biogenic amine contents were found to correlate with the free amino acids contents. The level of biogenic amines increased in accordance with decreasing free amino acids during storage (P<0.05). The cadaverine level reached a peak, 186.24mg/g, after 24h at ambient temperature, 371.98mg/g after 10 days at 10C, and 385.49mg/g after 20 days at iced temperature. Unacceptable levels were reached after 12h at ambient, 8 days at 10C and 16 days at 2C. Putrescine increased at a slower rate than histamine and cadaverine. The present study demonstrated the potential of cadaverine production as a quality indicator of M. nemurus during storage.